Importance of cellular immunity link for efficiency of replacement therapy in common variable immune deficiency - L. P. Sizyakina; I. I. Andreeva; D. I. Danilova (Медицинская иммунология, 2020)
Lifetime use of IgG replacement therapy  is the standard of CVID treatment. However, full control over stabilization of chronic infection loci is not always achieved, even if this therapy  is continuously applied. The purpose  of this study was to carry out comparative analysis of changes  in cellular  component of adaptive and  innate immune response, depending on effectiveness of replacement therapy  of patients with infectious CVID  phenotype. The  observation group  consisted of 15 patients with  CVID  who  were  diagnosed since early childhood in 100% of cases. They had prolonged respiratory infections followed by the development of complications requiring continuous treatment with antibiotics.After  reaching mean  age of 15 years  old,  the  intensity of infection-associated antibody deficiency was 6-8  times  per year. After verification of the  diagnosis, the  patients received  replacement therapy, first at the saturation dose,  and,  after stabilization of IgG  at the level of 7-8 g/l,  at the monthly maintenance dose. The clinical  course  of the disease was traced  during  a full year of replacement therapy, and the cellular  immunity indices  were evaluated. In all patients, after a year of therapy  corresponding to clinical  guidelines, there  was an improvement in quality  of life indices, decreased rates of recurrent bacterial infections. At the same time, 40% of them continued to suffer, on average, 5.4±1.1 times a year and required long-term courses of antibiotic therapy. Evaluation of immune status did not reveal statistically significant  differences in IgG plasma saturation between the groups of patients with different treatment efficiency: 8.7 (8-9) g/l and 9.1 (8.5-10.5) g/l, at p = 0.5. The  differences related  to immune cell factors  in cases of smaller  effect of IVIG  therapy  are manifested in higher  relative  numbers of T effectors  containing lytic Granzyme B granules  and CD14+CD284+  monocytes, accompanied by lower spontaneous active  oxygen forms produced by neutrophils, lesser contents of CD16+ natural killers in peripheral blood.The obtained data illustrate the value of monitoring, not only serum  IgG  level, but also the parameters of the  cellular  immune response. Such  analysis  may be essential  as a prognostic criterion for efficacy  of IVIG therapy. Reduced levels of some parameters of innate immunity cells serves a basis to formulate the concept of combined treatment and usage of tools that alter functions of immunocompetent cells.